2009
DOI: 10.1200/jco.2009.23.3734
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib Combined With Letrozole Versus Letrozole and Placebo As First-Line Therapy for Postmenopausal Hormone Receptor–Positive Metastatic Breast Cancer

Abstract: This trial demonstrated that a combined targeted strategy with letrozole and lapatinib significantly enhances PFS and clinical benefit rates in patients with MBC that coexpresses HR and HER2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
635
1
21

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 955 publications
(672 citation statements)
references
References 35 publications
15
635
1
21
Order By: Relevance
“…30,31 Recently, it has been shown that a combination of trastuzumab and hormonal therapy is superior than hormonal therapy alone. [32][33][34] However, the question of relative resistance to trastuzumab therapy in ER þ /HER2 þ tumors still remains. Whether this is because of ER and HER2 cross-talk only or other growth factor receptors are also involved is a subject of active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Recently, it has been shown that a combination of trastuzumab and hormonal therapy is superior than hormonal therapy alone. [32][33][34] However, the question of relative resistance to trastuzumab therapy in ER þ /HER2 þ tumors still remains. Whether this is because of ER and HER2 cross-talk only or other growth factor receptors are also involved is a subject of active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer patients with oestrogen receptor-positive tumours revealing HER-2 amplification have been shown to respond poorly to endocrine therapy with aromatase inhibitors as well as tamoxifen. 147 Adding trastuzumab 148 or lapatinib 149 in concert improves response to aromatase inhibitors. The finding that mTOR inhibition may reverse resistance to endocrine agents in breast cancer MCF-7 cells 150,151 is consistent with clinical findings; recently, two studies reported addition of the mTOR inhibitor everolimus to endocrine therapy with the aromatase inhibitor exemestane 152 or the anti-oestrogen tamoxifen, 153 to significantly improve response to therapy in cancers nonamplified for HER-2.…”
Section: Activating Mutations In the Pten/pi3k/mtor Pathway As A Causmentioning
confidence: 99%
“…However, these approaches have shown limited efficacy; in fact, fulvestrant only elicits a response in approximately 7% of ERa-positive tumors that regrow under AI therapy, although its clinical use is justified based on a clinical benefit rate of 32% (Chia et al, 2008). On the other hand, trials with combinations of AIs and growth factor signal inhibitors have not improved outcomes in most cases , except for recent results on novel combinations that are still under research (Baselga et al, 2009;Johnston et al, 2009). In this scenario, the dynamic profiles of our model coincide with previous findings concerning the relevance of growth factor signaling but, importantly, our data also support a different explanation of the role of ERa: firstly, the switch from pS118-to pS167-ERa, an isoform known to be related to MAPK/AKT signaling (Campbell et al, 2001), may indicate that sustained ERa expression is more a consequence of the activation of other pro-growth signals than a reflection of the importance of canonical ERa function; secondly, the fact that both over-and underexpressed gene sets during MCF7-LTED adaptation showed infra representation of ERa-responsive elements and were not enriched in 17bE2-mediated regulation from original MCF7 data (Carroll et al, 2006), suggests a molecular landscape in which ERa, despite sustained expression, is no longer a highly active transcription modulator.…”
Section: Effect Of 17be2 Through Eramentioning
confidence: 99%